Effect of maternal antioxidant supplementation and/or exercise practice during pregnancy on postnatal overnutrition induced by litter size reduction: Brain redox homeostasis at weaning. Issue 71 (December 2018) - August, Pauline Maciel; Maurmann, Rafael Moura; Saccomori, André Brum; Scortegagna, Mariana Crestani; Flores, Eduardo Borges; Klein, Caroline Peres; dos Santos, Bernardo Gindri; Stone, Vinicius; Dal Magro, Bárbara Mariño; Cristhian, Leo; Santo, Carolina Nunes; Hözer, Régis; et al.
Highlights: Maternal interventions do not cause alterations in the maternal outcome and offspring growth. Litter size reduction enhanced fat mass and body weight at weaning. Encephalic structures present altered antioxidant enzymes activities in response to litter size reduction. When maternal exercise and naringenin supplementation were allied, most of the effects disappeared. Abstract: Prenatal and early postnatal environments can permanently influence health throughout life. Early overnutrition increases the risk to develop chronic diseases. Conversely, the intake of flavonoids and exercise practice during pregnancy seem to promote long-term benefits to offspring. We hypothesized that benefic interventions during pregnancy could protect against possible postnatal neurochemical alterations caused by overnutrition induced by reduced litter size. Female Wistar rats were divided into four groups: (1) sedentary + vehicle, (2) sedentary + naringenin, (3) swimming exercise + vehicle, and (4) swimming exercise + naringenin. One day after birth, the litter was culled to 8 pups (control) or 3 pups (overfed) per dam, yielding control and overfed subgroups for each maternal group. Serum of 21-days-old pups was collected, also the cerebellum, hippocampus, and hypothalamus were dissected. Litter size reduction increased fat mass and enhanced body weight. Maternal interventions, when isolated, caused reduced glucose serum levels in offspring nurtured in control litters. In the cerebellum, reducing the litter size decreased the activity of thioredoxin reductase, which was prevented by maternal supplementation with naringenin. Hippocampus and hypothalamus have shown altered antioxidant enzymes activities in response to litter size reduction. Interestingly, when maternal exercise and naringenin supplementation were allied, the effect disappeared, suggesting a concurrent effect of the two maternal interventions. In conclusion, exercise or naringenin supplementation during pregnancy can be important interventions for combating the increasing rates of overweight during the infancy and its related neurochemical changes, especially when applied isolated.